New Solutions for Forming Database of State Cadasters of Buildings and Constructions Based on Geoinformation Programs. (Eurasian Scientific Herald, 2023)
The article describes the creation, optimization and rational use of a system that provides the current state, dynamics and changes of location indicators by conducting state cadastral works of buildings and structures using modern mapping technologies based on geoinformation systems, and the scope of work of state cadastral works of buildings and structures and issues such as serving in solving productivity problems are covered.